Urgensi supervisi pendidikan dalam pengembangan pofesionalisme guru dan mutu pembelajaran - Agus Yasin; Galang Reformasi Al-Amien; Liza Latnasari (At Turots: Jurnal Pendidikan Islam, 2023)
Various problems that exist in the world of education require improvement in order to improve the quality of education for the better, the development of the quality of education is determined by the process and results of teaching and learning activities, teaching activities will be appropriate if the executors of these activities know all the provisions that must be carried out, the teacher is the first key in the success of teaching and learning activities, a teacher will develop with supervision who supervises and guides each teacher so that they can understand and understand everything that is needed during the learning process, with educational supervision the potential of teachers is developed to become professional teachers who can develop quality learning. The purpose of this research is to find out the urgency of educational supervision in the development of teacher professionalism and the quality of learning, with this it can be seen that supervision has a role as supervisor, guide, and trainer for all each teacher to be able to develop the quality of learning and education.